Actual problems and new opportunities in journalism (Herald of Journalism, 2020)
The article investigates the effects of modern technology and new opportunities on journalism. Today, some believe that despite its many advantages, digital technologies are being used more as tools for keep- ing people at a distance than truly engaging them by bringing ideas and people together. Journalism as it develops digitally might be seen as a microcosm of these concerns. The pressure to change is strong, but with journalism as well as other facets of social life, there are equal and opposite forces attempting to re-establish old norms, power structures and process- es. Standards applied to online and digital journalism and the journalist’s work in social networks, require further study.
Keywords: modern technology, digital journalism, Internet, Online journalism, social networks, media.